Arabian nights : The marvels and wonders of the thousand and one nights - Burton, Richard Francis; Richard F. Burton; Jack Zipes; Daniel Beaumont (New York : Signet Classics, 2007)
Upon learning of his queen's infidelity, proud King Shahryar has her killed. As revenge on man kind, he decides to wed a different virgin every night, only to have her beheaded at dawn. Such as Shahryar's practice for three thousand nights, but then he weds Scheherazade, the maiden who will change his life. A breath king beauty, Scheherazade is as learned as she sensuous. Her first night with Shahryar, she uses her imagination, eloquence, and cunning to regale him with a legend of genies and wishes , wisely cutting the story short at dawn. The king is so beguiled , he cannot have her murdered without hearing the tale's end. From then on, Scheherazade spends nights conjuring stories of flying carpets and fantastic journeys ,always stopping with a cliff hanger and saving her own life with such adventure as the voyage of Sinbad " Ali baba and the Forty Thieves", "Aladdin and the magic lamp" and many others. This edition has follow the 1885-86 unexpurgated translation of Richard F. Burton. Intricate and inventive , these stories within a story continue to captivate readers as they have for centuries.
English